Regulation of synthesis of guanosine 3':5'-cyclic monophosphate in neuroblastoma cells. - Bartfai, T (1978)
The increase in intracellular cyclic GMP concentrations in response to muscarinic-receptor activation in N1E-115 neuroblastoma cells is dependent on extracellular Ca2+ ion. The calcium ionophore A23187 can also evoke an increase in cyclic GMP in the presence of Ca2+ ion. Most (about 85%) of the guanylate cyclase activity of broken-cell preparations is found in the soluble fraction. The soluble enzyme can utilize MnGTP (Km = 55 micrometer), MgGTP (Km = 310 micrometer) and CaGTP (Km greater than 500 micrometer) as substrates. Free GTP is a strong competitive inhibitor (Ki approximately 20 micrometer). The enzyme possesses an allosteric binding site for free metal ions (Ca2+, Mg2+ and Mn2+). The membrane-bound guanylate cyclase is qualitatively similar to the soluble form, but has lower affinity for the metal-GTP substrates. Entry of Ca2+ into cells may increase cyclic GMP concentration by activating guanylate cyclase through an indirect mechanism.